PERAN MENYIMAK DALAM MENGEMBANGKAN KETERAMPILAN BERBAHASA - Chindytia; Maria Goreti Rini Kristiantari; I Komang Agus Mahendra; I Gede Sandipa Bima Yuda; Kadek Agastya Mahardika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine in depth the role of listening skills in developing students’ language abilities. The issue addressed is the lack of attention given to listening instruction compared to other language skills, such as reading and writing, even though listening is a fundamental component in the language acquisition process. This research employs a qualitative method with a literature study approach by analyzing various sources such as journals, books, and relevant previous studies. The results indicate that listening skills play a fundamental role in supporting the development of speaking, reading, and writing abilities. Through listening, individuals can obtain information, enrich their vocabulary, and better understand language structures. Listening skills also contribute to the development of cognitive abilities, such as comprehension, analysis, and interpretation of received information. In its implementation, listening instruction requires interactive strategies, the use of varied learning media, and adjustments to students’ characteristics to be more effective. It can be concluded that listening skills have a very important role in improving overall language proficiency.